Adult Onset Nesidioblastosis Treated by Subtotal Pancreatectomy - Gupta, Rahul Amreesh; Patel, Roma Prahladbhai; Nagral, Sanjay (JOP. Journal of the Pancreas, 2013)
Context Nesidioblastosis is a rare cause of non insulinoma pancreatogenous hypoglycemic syndrome seen in adults. It is characterized by postprandial hypoglycemia with high insulin and C-peptide levels without any detectable pancreatic lesion. The definitive diagnosis can be made only on histopathological examination of the resected specimen. Case report We report a case of a 50-year-old lady presenting with hypoglycemic attacks being misdiagnosed preoperatively as insulinoma and treated with enucleation leading to recurrence of symptoms after 6 months. Later medical therapy was tried which failed and patient needed subtotal pancreatectomy for resolution of symptoms. Conclusion Nesidioblastosis should be suspected in patients with endogenous hyperinsulinemic hypoglycemia without any detectable pancreatic tumor on preoperative imaging. Image: Pancreatic ductal epithelium showing vacuolated neuroendocrine cells.